2002
DOI: 10.3201/eid0802.010314
|View full text |Cite
|
Sign up to set email alerts
|

Distemper Outbreak and Its Effect on African Wild Dog Conservation

Abstract: In December 2000, an infectious disease spread through a captive breeding group of African wild dogs (Lycaon pictus) in Tanzania, killing 49 of 52 animals within 2 months. The causative agent was identified as Canine distemper virus (CDV) by means of histologic examination, virus isolation, reverse transcriptase-polymerase chain reaction analysis, and nucleotide sequencing. This report emphasizes the importance of adequate protection against infectious diseases for the successful outcome of captive breeding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
63
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 11 publications
3
63
0
4
Order By: Relevance
“…Van de Bildt et al (2002) observed the same results with CDV in African wild dog in Tanzania. Canine distemper is a very common disease in suburban and farm dogs in Brazil because of the absence of vaccination.…”
Section: Ef418783 [Lederle]) and Rinderpest Virus (Outgroup: Ef186supporting
confidence: 76%
See 1 more Smart Citation
“…Van de Bildt et al (2002) observed the same results with CDV in African wild dog in Tanzania. Canine distemper is a very common disease in suburban and farm dogs in Brazil because of the absence of vaccination.…”
Section: Ef418783 [Lederle]) and Rinderpest Virus (Outgroup: Ef186supporting
confidence: 76%
“…In many parts of the world, dogs are the likely maintenance host and represent a source of CDV to wildlife. Canine distemper originating from dogs has been reported in lions in Serengeti (Roelke-Parker et al, 1996), Baikal seals (Phoca sibirica) in Siberia (Mamaev et al, 1995), crabeater seals (Lobodon carcinophaga; Bengston et al, 1991), and African wild dogs (Lycaon pictus; Van de Bildt et al, 2002).…”
mentioning
confidence: 99%
“…(31). However, concerns remain about the vulnerability of critical populations, such as African wild dogs (45). Our results suggest that, as a conservation measure to protect wildlife, mass domestic dog vaccination efforts need to be continuous and widespread, posing logistic and financial challenges, and, even then, are unlikely to result in the elimination of infection in wildlifeprotected areas.…”
Section: Discussionmentioning
confidence: 91%
“…Desse modo, esse cão representa um risco direto de transmissão da cinomose para os animais silvestres. Impacto negativo desta virose sobre populações de carnívoros selvagens já é relatado ( Van de Bildt et al 2002). Uma epidemia no Serengueti acometeu 30% de uma população de 3000 leões africanos, muitos dos quais apresentavam mioclonia, e até 50% dos que apresentaram sinais clínicos podem ter morrido (Harder et al 1995, Roelke-Parker et al 1996.…”
Section: Resultsunclassified